Pengaruh Sistem Informasi Akuntansi dan Persepsi Kegunaan Terhadap Minat Penggunaan E-Wallet dengan Kepercayaan Pengguna Sebagai Variabel Moderasi - I Komang Danu Putra; Putu Purnama Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Advances in digital technology have driven the increased use of e-wallets as a payment method, considered more practical, faster, and safer. However, public interest in using e-wallets is influenced by several factors, such as the quality of accounting information systems, perceived usability, and user trust. This study aims to examine the influence of accounting information systems and perceived usability on e-wallet use interest and to assess the role of user trust as a moderating variable. The study was conducted on MSMEs in Denpasar City using a quantitative approach by distributing questionnaires to 100 respondents. Data analysis used the Partial Least Square (PLS) method. The results revealed that the accounting information system has a positive and significant effect on interest in using e-wallets. Perceived usefulness also showed a significant positive effect on interest in use. In addition, user trust was able to strengthen the relationship between the accounting information system and perceived usefulness with interest in using e-wallets. Overall, these findings confirm that the better the quality of accounting information, the greater the perceived benefits, and the higher user trust, the greater the interest of MSMEs and the public in using e-wallets. This study is expected to provide a basis for consideration for e-wallet service providers in improving system quality, service features, and security aspects to foster user trust.